Year-round Satellite Multi Frequency Synthetic Aperture Radar Observations During the MOSAiC Expedition - Singha, Suman; Spreen, Gunnar; Krumpen, Thomas; Davidson, Malcolm; Sobue, Shinichi; Howell, Stephen; Kwok, Ron; Zecchetto, Stefano; Gonzáles Bonilla, María José; Frulla, Laura; Kim, Hyun-Cheol; Toyota, Takenobu; et al. (2020)
In September 2019, the ambitious multidisciplinary Arctic MOSAiC expedition (Multidisciplinary drifting Observatory for the Study of Arctic Climate) started. The research icebreaker Polarstern got anchored to an ice floe in the central Arctic for a complete seasonal cycle (with minimal interruption) drifting with the ice. The expedition provides a unique opportunity for the researchers to better understand and quantify relevant interactive processes within the atmosphere–ice–ocean system that impact the sea ice properties and dynamics. In order to fulfill this aim comprehensive coincident in-situ, airborne and satellite measurements are necessary. In the presence of Arctic winter and frequent cloud coverage over the study area, Synthetic Aperture Radar (SAR) has proven to supply very useful datasets to observe the sea ice properties and dynamics at higher spatial and temporal resolution. Through an outstanding collaboration between different space agencies and research institutes, initiated by the WMO Polar Space Task Group, a unique and comprehensive collection of SAR acquisitions mainly targeting the MOSAiC Central Observatory (CO) was collected during the complete year of the drift. SAR images from several sensors and at frequencies, in X-band (TerraSAR-X/TanDEM-X, PAZ, COSMO-SkyMed, KOMPSAT-5), C-band (Sentinel-1, RADARSAT-2, RCM) and L-band (ALOS-2, SAOCOM) in different imaging modes and polarizations were acquired. Some of the sensors provide daily or sub-daily coverage of the MOSAiC CO and thus close to co-incident observations at different frequencies can be achieved. The advantages for ice property retrieval at different frequencies can be exploited and directly compared with in-situ and airborne observations. Here we will present our unique collection of multi-frequency SAR datasets and some initial results on sea ice properties retrieval from the first months of the expedition.